Being in the Right Place at the Right (and Bad) Time Analysis of CEO Rewards for Luck before and after the Credit Crunch - Hadincová, Ludmila; Navrátil, David; Špecián, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
Diploma thesis tests the existence of luck premium on U.S. CEOs' compensations. Luck premium means that in case of high principal-agent costs, CEOs are rewarded for random luck and not only for their productivity. Thesis uses financial crisis in 2008 as a breaking event after which attention and control of CEOs' remuneration by owners, public, and media intensified. Using regression with fixed effects on panel data between years 2004 and 2012 thesis proved impact of luck premium before 2008 while the influence was not significant after 2008. Results were not robust for other model specifications, which might be caused by selectivity of the dataset. Thesis then presents overview of theoretical approaches to CEOs' compensation analysis and recommendations for optimal compensation set-up.
Vedoucí práce: David Navrátil
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses